Yield of strawberry crops under different irrigation levels and biofertilizer doses (Revista Ciência Agronômica, 2018)
Strawberry is produced and appreciated in different regions of the world, due to its productive andcommercial characteristics. Biofertilizer is an organic fertilizer that is easy to prepare and effective to nourish plants. Theobjective of this work was to assess the effect of different irrigation levels and anaerobically fermented bovine biofertilizerdoses, on biomass accumulation and strawberry crop yield. The experiment was carried out in the experimental area ofthe UFC, in Fortaleza, Ceará, Brazil, from August to December 2012, under a screened environment. The experimentaldesign was randomized blocks designed into subdivided plots, in which irrigation levels were applied via drip irrigation(equivalent to 33.3, 66.6, 100, 133.3 and 166.6% of the evaporation measured in the Class A tank - ECA), correspondingto the plots. The four doses of bovine biofertilizer (125, 250, 375 and 500 mL plant-1 week-1) were the subplots, with fourreplications. The assessed parameters were: biomass (root, shoot and total dry matter), fruit diameter, fruit length, numberof fruits per plant, average fruit mass and yield. The biofertilizer and irrigation increased strawberry shoot biomass andtotal biomass. The interaction between irrigation and bovine biofertilizer raised the root matter to 3.7 g. The biofertilizerwas nutritionally efficient for the strawberry regarding number of fruit, fruit diameter and yield. Irrigation increasedstrawberry length and average mass.